Computed tomographic study of anatomical relationship between pubic symphysis and ischial spines to improve interpretation of intrapartum translabial ultrasound. (December 2016) - Arthuis, C. J.; Perrotin, F.; Patat, F.; Brunereau, L.; Simon, E. G.
ABSTRACT: Objective: To analyze the anatomical relationship between the pubic symphysis and the ischial spines to determine reliable landmarks for the assessment of fetal head descent by intrapartum translabial ultrasound (ITU). Methods: All computed tomography (CT) scans performed for breech presentation and for twin delivery between 2006 and 2014 in a tertiary university hospital were obtained for measurement and analysis by two operators. The symphysis–left ischial spine angle (SIA) and the symphysis–left ischial spine distance (SID) were measured on three‐dimensional reconstructions from the CT volume dataset. We calculated intra‐ and interobserver agreements for SIA and SID with 95% prediction intervals, created Bland–Altman plots with 95% limits of agreement and estimated the intraclass correlation coefficient (ICC). A sagittal plane projection from the SIA enabled calculation of a sagittal angle, corresponding to the angle of progression (AoP) on ITU. Results: SIA and SID were obtained from CT images from 458 women. Reproducibility was good for both SIA (intraobserver ICC, 0.94 (95% CI, 0.88–0.97) and interobserver ICC, 0.81 (95% CI, 0.66–0.92)) and SID (intraobserver ICC, 0.92 (95% CI, 0.82–0.97) and interobserver ICC, 0.83 (95% CI, 0.73–0.92)). The median SIA was 106° (interquartile range (IQR), 105–109° ) and median SID was 26.1 (IQR, 23.4–29.5) mm. SIA and SID were not correlated with pelvic diameter or height. The 50 th percentile of AoP was 110°. Conclusion: Knowledge of the anatomical relationship between the pubic symphysis and ischial spines makes it possible to establish a sonographic method for assesssing fetal head descent by taking into account the level of the ischial spines. Copyright © 2015 ISUOG. Published by John Wiley & Sons Ltd.